From two-dimensional materials to their heterostructures: An electrochemist's perspective. (September 2017) - Velický, Matěj; Toth, Peter S.
Graphical abstract: Highlights: Recent progress in the research on two-dimensional (2D) materials is reviewed. Properties of 2D materials are discussed in the context of electrochemistry. The review is focused on transition metal dichalcogenides and 2D heterostructures. Promising emerging trends and strategies are highlighted. Abstract: Two-dimensional (2D) materials have, within just one decade, reshaped many disciplines of modern science and technology, both through intensive fundamental research and early commercial applications. In this review, we will provide a comprehensive summary of the properties, synthesis, characterisation, and application of 2D materials in the context of electrochemistry and related scientific fields. Firstly, the structural, electronic, optical, and mechanical properties, and a variety of preparation and characterisation techniques of 2D materials are presented. Secondly, current electrochemical understanding of 2D and layered materials and their modification is discussed. Lastly, future perspectives and new frontiers in optoelectronics, photocatalysis, and renewable energy using 2D materials are outlined. Our primary focus is on group 6 transition metal dichalcogenides (TMDCs) and other emerging 2D materials beyond graphene, including their heterostructures. These nanomaterials are essential for the next generation of devices in tuneable electrochemistry, sensing, and photovoltaics. Although broad in scope, this review is not an exhaustive list of facts; rather, it summarises the established knowledge and pinpoints the most promising future trends. It is aimed at readers with background in electrochemistry wanting to broaden their perspective or initiate research on 2D materials as well as those with 2D materials expertise looking to work on electrochemistry-based applications, such as energy storage and conversion.